Force profile of functional leg muscle groups in curve sprinting - preliminary results - Funken, J.; Zedler, M.; Lüdorff, S.; Alt, T.; Heinrich, K.; Potthast, W. (ISBS Proceedings Archive (Michigan), 2023)
Research on lower extremity joint and muscle kinetics in athletic curve sprinting is under-represented in the scientific literature. This is an issue due to its importance for training and rehabilitation protocols as well as for injury prevention. In this study, we analysed six male sprinters regarding their force profile of functional lower extremity muscle groups in curve sprinting. Three-dimensional motion capture (Vicon) and four force plates (Kistler) were used to capture kinematic and kinetic data. Inverse dynamic calculations (Anybody), including muscle forces, provide first insights into potential side differences of leg muscle group force profiles between the inside and the outside leg in submaximal curve sprinting (9.48 ± 0.26 m/s). However, a differentiated analysis of individual muscles is necessary in the future as grouping might overlay the side-specific effects in particular muscles.